Self-Reliant Quality of Life Development for the Elderly A Case Study of Taphanhin Municipality Taphanhin District, Phichit Province - Phukhammee, Parinrit; Bodeerat , Chot; Donkjan, Phatsakorn (Academic MCU Buriram Journal, 2025)
The objective of this research is to study the quality of life of self-reliant elderly individuals, compare their quality of life, and explore approaches for improving their well-being. A mixed-methods research approach, combining quantitative and qualitative methods, was employed.For the quantitative aspect, the study population consisted of 359 individuals aged 60 and above residing in the municipal area of Taphanhin, Taphanhin District, Phichit Province. The research instrument used was a questionnairewith a reliability coefficient of 0.928 and statistical analysis included percentage, mean, standard deviation, and hypothesis testing using T-test and F-test.For the qualitative aspect, 6 key informants were interviewed to gather their opinions on ways to enhance the quality of life for self-reliant elderly individuals. The qualitative data were analyzed using content analysis, supported by relevant concepts and theories. The research results found that: 1. The overall quality of life of self-reliant elderly individuals in Taphanhin Municipality across six aspects : Sensory Abilities, Autonomy, Past Present and Future Abilities, Social Participation, Death and Dying, Intimacy was at a moderate level. 2. Personal factors such as age, marital status, education level, average monthly income, occupation, and household size influenced differences in the quality of life. However, gender and length of residence in the area did not significantly affect the quality of life. 3. The key challenge in improving the quality of life for self-reliant elderly individuals was their ability to travel and participate in various life-enhancement activities organized by relevant agencies. To address this, increasing the number of trained caregivers (Caregivers or CGs) to support personal healthcare, physical therapy, and nutrition, as well as facilitating transportation for elderly individuals to attend development programs, would be beneficial. Additionally, organizing specialized programs tailored to the needs of the elderly could encourage greater participation, ultimately leading to an improved quality of life.